ALIGNING DIGITAL TEACHING MATERIALS WITH PERSONALIZED SYSTEM of INSTRUCTION MODEL IN PHYSICAL EDUCATION - Silvy Juditya; Adang Suherman; Amung Ma’mun; Agus Rusdiana (Journal of International Conference Proceedings (JICP), 2019)
The development of the digital era requires a breakthrough in the learning process physical education. This to a paradigm shift in the learning process from used traditional media that become uses digital media. The use of digital teaching materials has been applied in several subjects, but the use of digital teaching materials is still limited in physical education learning. To optimize the use of digital teaching materials in learning physical education a supportive learning model is needed. Personalized system of instruction (PSI) is one of the learning models that becoming with the digital teaching materials in physical education learning. This study purpose describe application digital teaching materials in aligned with personalized system of instruction model (PSI).